Pharmacological Properties of Trichostatin A, Focusing on the Anticancer Potential: A Comprehensive Review - Abdelhakim Bouyahya; Nasreddine El Omari; Mohamed Bakha; Tarik Aanniz; Naoual El Menyiy; Naoufal El Hachlafi; Aicha El Baaboua; Mohamed El-Shazly; Mohammed Merae Alshahrani; Ahmed Abdullah Al Awadh; Learn-Han Lee; Taoufiq Benali; et al. (MDPI AG, 2022)
Trichostatin A (TSA), a natural derivative of dienohydroxamic acid derived from a fungal metabolite, exhibits various biological activities. It exerts antidiabetic activity and reverses high glucose levels caused by the downregulation of brain-derived neurotrophic factor (BDNF) expression in Schwann cells, anti-inflammatory activity by suppressing the expression of various cytokines, and significant antioxidant activity by suppressing oxidative stress through multiple mechanisms. Most importantly, TSA exhibits potent inhibitory activity against different types of cancer through different pathways. The anticancer activity of TSA appeared in many in vitro and in vivo investigations that involved various cell lines and animal models. Indeed, TSA exhibits anticancer properties alone or in combination with other drugs used in chemotherapy. It induces sensitivity of some human cancers toward chemotherapeutical drugs. TSA also exhibits its action on epigenetic modulators involved in cell transformation, and therefore it is considered an epidrug candidate for cancer therapy. Accordingly, this work presents a comprehensive review of the most recent developments in utilizing this natural compound for the prevention, management, and treatment of various diseases, including cancer, along with the multiple mechanisms of action. In addition, this review summarizes the most recent and relevant literature that deals with the use of TSA as a therapeutic agent against various diseases, emphasizing its anticancer potential and the anticancer molecular mechanisms. Moreover, TSA has not been involved in toxicological effects on normal cells. Furthermore, this work highlights the potential utilization of TSA as a complementary or alternative medicine for preventing and treating cancer, alone or in combination with other anticancer drugs.